한국판 스마트폰 사용에 대한 상위인지 질문지(K-MSUQ) 타당화 연구 - 김현지 (The Graduate School, Ajou University, 2024)
본 연구는 국내 대학생을 대상으로 스마트폰 사용에 대한 상위인지 질문지(The Metacognitions about Smartphone use Questionnaire: MSUQ)를 타당화하고, 사회불안과 문제성 스마트폰 사용의 관계에서 스마트폰 사용에 대한 상위인지와 지각된 사회적 지지의 조절된 매개효과를 확인하였다. 연구 1은 스마트폰 사용에 대한 상위인지 질문지 (MSUQ)를 타당화하였다. 19~29세 대학생 400명을 대상으로 탐색적 요인분석과 확인적 요인분석을 실시하였다. 그 결과 한국판 스마트폰 사용에 대한 상위인지 질문지 (K-MSUQ)는 긍정적 상위인지와 부정적 상위인지로 구성되는 2 요인 모형으로 나타났고, 적절한 모형 적합도를 보였다. 본 척도는 높은 내적 합치도를 보였다. 또한 K-MSUQ 는 역기능적 상위인지 질문지 단축형(MCQ-30)과 수렴 타당도를 나타냈고, 성인 스마트폰 중독 자가 진단 척도(S-척도)와 공존 타당도를 보였다. 문제성 스마트폰 사용에 대한 K-MSUQ의 증분 타당도를 확인한 결과, 부정적 상위인지만 유의하게 성인 스마트폰 중독 자가 진단 척도(S-척도)를 예측하는 것으로 나타났다. 연구 2는 19~29세 대학생 250명을 대상으로 사회불안과 문제성 스마트폰 사용의 관계에서 스마트폰 사용에 대한 상위인지와 지각된 사회적 지지의 조절된 매개효과를 검증하였다. 지각된 사회적 지지는 오프라인과 온라인으로 나누어 조절효과를 살펴보았다. 그 결과, 사회불안과 문제성 스마트폰 사용의 관계에서 긍정적 상위인지의 매개효과가 유의미하지 않아, 병렬 매개효과는 검증 되지 않았다. 반면, 사회불안과 문제성 스마트폰 사용의 관계를 부정적 상위인지가 부분 매개하였으며, 이를 오프라인 사회적 지지가 정적으로 조절하는 것으로 나타났다. 그러나 온라인 사회적 지지의 조절효과는 나타나지 않았다. 마지막으로 본 연구의 의의와 제한점에 대해 논의하였다.|This study validated the Metacognitions about Smartphone Use Questionnaire (MSUQ) on Korean college students and examined the moderated mediating effects of metacognitions about smartphone use and perceived social support on the relationship between social anxiety and problematic smartphone use (PSU). In Study 1, the MSUQ was validated with 400 university students (Female = 50%; mean age = 23.27 + 2.39; age range = 19-29). We a randomly allocated 200 participants each for an exploratory factor analysis(EFA) and confirmatory factor analysis(CFA). The exploratory and confirmatory factor analyses revealed a two-factor structure for the Korean version of the MSUQ (K-MSUQ), consisting of positive metacognitions and negative metacognitions about smartphone use, and showed good model fit. The scale showed high internal consistency. In addition, the K-MSUQ showed convergent validity with the Metacognitions Questionnaire-30 (MCQ-30) and concurrent validity with the Adult Smartphone Addiction Self-Diagnosis Scale (S-scale). Regarding the incremental validity of the K-MSUQ for problematic smartphone use, only negative metacognitions significantly predicted the PSU. Study 2 investigated the moderated mediating effects of metacognitions about smartphone use and perceived social support on the relationship between social anxiety and PSU. Perceived social support was divided into offline and online support to examine the moderating effect. Participants were 250 college students (Female = 62.4%; mean age = 23.64 + 2.34; age range = 19-29). The results revealed that the mediating effect of positive metacognitions about smartphone use was not significant, and parallel mediation was not supported. On the other hand, the partial mediating effect of negative metacognitions was found, and offline social support positively moderated the mediating effect of negative metacognitions on the relationship between social anxiety and PSU. However, the moderating effect of perceived online social support was not found. Finally, we discussed the significance and limitations of this study.
학위논문(석사)--심리학과,2024. 8
Keywords: S-REF 모형; 문제성 스마트폰 사용; 사회불안; 스마트폰 사용에 대한 상위인지; 지각된 오프라인 사회적 지지; 지각된 온라인 사회적 지지